Pembangunan kawasan sekitar : implikasi ke atas struktur sosio demografi ciri-ciri sosio ekonomi penduduk di Skim Penempatan Semula Batu 4 1/2 Batu Kawa, Kuching - Dorisi, Ak Resit. (Universiti Malaysia Sarawak (UNIMAS), 2002)
The study will focusing on the characteristic aspects of the socio demographic, socio economic and the problem faced by the residents at Batu Kawa Resettlement S heme Area near mile 4 1/2 Kuching. The study will also seek the relationship between the dependent and independent variables. Basically, throughollt the study a majority number of respondents have a positive perception forwards the effect and the con, equences the development upon their area.